The Effect of Population Growth upon the Quantity of Education Children Receive: A Comment - Meeks, T. J. (The Review of Economics and Statistics, 1982)
Malthusian theory asserts that high population growth in poor countries retards economic development. 2 authors Simon and Pilarski have recently challenged this theory on the basis of their own research; it is their contention that previous studies of population growth and education (1 of the principal modes by which the Malthusian mechanism is assumed to operate) have been flawed. The defect is felt to lie in the assumption of simple rather than partial associations of the 2 variables education and population growth. On the basis of their tightened specifications they have found demographic variables to be nonsignificant in explaining educational expenditures per child once other relevant regressors have been introduced. Similarly little effect of the demographic variable on primary and tertiary school enrollment rates were found although an effect for secondary school enrollment rates was found. On examination of the theoretical framework and the several explanatory variables however the author concludes that a crucial variable which is sure to have a vital bearing on the conclusions reached has been misspecified in the equations. Further the author asserts that a more thorough specification of the tests of the hypothesis (i.e. that high population growth retards educational investment) actually provides additional support for the Malthusian conclusion on educational expenditures despite unpromising initial indications.